MALAYSIA’S COMMITMENT TO THE GENEVA CONVENTIONS: APPLICATION AND CHALLENGES - Mazura Md Saman; Khairul Nizam Taib; Salma Yusof; Shaharudin Abdul Rahman (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This article offers a constructive perspective on the application of the 1949 Geneva Conventions in Malaysia. It aims to address the Malaysian government’s commitment to the Conventions and how that plays out in the local specific circumstances id est insurgency, the confrontation with Indonesia and the incursion of militants in Lahad Datu. Sabah. Malaysian Armed Forces (MAF) also gained the opportunity to value the Convention during international theatre assignments under the United Nations (UN) Flag. Local stakeholders closely monitor the dissemination of International Humanitarian Law (IHL) to ensure Armed and Security Forces properly understand the Conventions’ spirit. The research methodology involves a qualitative content analysis of legislative framework, case law, and secondary archival data on the application of the Geneva Conventions and related treaties. The study suggests that Malaysia closely observed respect for the IHL in dealing with armed conflicts.